Pemikiran Ibnu Qoyyim tentang Proteksi Minat dan Motivasi Belajar dalam Kitab Ad-daa’ wa Ad-dawaa’ - Hasibuan, Hilman Rizky; Panjaitan, Ratna Wati (Prodi PAI STAI Sumatera Medan, 2020)
Interest and motivation have a great influence on the learning process. In Indonesia, interest and motivation to learn is still low, as seen from the results of research on the Program for International Student Assessment (PISA) which shows that the level of literacy in Indonesia is very low compared to countries in the world. Since the population of Indonesia is 85% Muslim, it can be said that those who have low interest and motivation to learn are the majority of Muslims. To answer this problem, in order to find out the methods of safeguarding and preventive measures regarding interest and motivation to learn that are suitable for the Islamic Ummah in Indonesia, we study a book entitled Ad-Daa 'Wa Ad-Dawaa' written by Ibnu Qoyyim. This study uses the type of library research with descriptive and analytical content analysis techniques on the book Ad-Daa 'Wa Ad-Dawaa'. This study concludes that the most important thing for a knowledge seeker is to maintain the condition of the heart that is accompanied by faith and piety. Hearts that are sick and far from faith and piety are the main causes of the lack of interest and motivation to do something good, including learning.